Strigolactones modulate stem length and diameter of cherry rootstocks through interaction with other hormone signaling pathways - Liu, Xunju; Xu, Yan; Sun, Wanxia; Wang, Jiyuan; Gao, Yixin; Wang, Lei; Xu, Wenping; Wang, Shiping; Jiu, Songtao; Zhang, Caixi (Frontiers in Plant Science, 2023)
Stem growth and development has considerable effects on plant architecture and yield performance. Strigolactones (SLs) modulate shoot branching and root architecture in plants. However, the molecular mechanisms underlying SLs regulate cherry rootstock stem growth and development remain unclear. Our studies showed that the synthetic SL analog rac-GR24 and the biosynthetic inhibitor TIS108 affected stem length and diameter, aboveground weight, and chlorophyll content. The stem length of cherry rootstocks following TIS108 treatment reached a maximum value of 6.97 cm, which was much higher than that following rac-GR24 treatments at 30 days after treatment. Stem paraffin section showed that SLs affected cell size. A total of 1936, 743, and 1656 differentially expressed genes (DEGs) were observed in stems treated with 10 μM rac-GR24, 0.1 μM rac-GR24, and 10 μM TIS108, respectively. RNA-seq results highlighted several DEGs, including CKX, LOG, YUCCA, AUX, and EXP, which play vital roles in stem growth and development. UPLC-3Q-MS analysis revealed that SL analogs and inhibitors affected the levels of several hormones in the stems. The endogenous GA3 content of stems increased significantly with 0.1 μΜ rac-GR24 or 10 μΜ TIS108 treatment, which is consistent with changes in the stem length following the same treatments. This study demonstrated that SLs affected stem growth of cherry rootstock by interacting with other hormone signaling pathways. These results provide a solid theoretical basis for using SLs to modulate plant height and achieve sweet cherry dwarfing and high-density cultivation.